Red Flags, Prognostic Impact, and Management of Patients With Cardiac Amyloidosis and Aortic Valve Stenosis: A Systematic Review and Meta-Analysis - Myasoedova, Veronika A.; Conte, Maddalena; Valerio, Vincenza; Moschetta, Donato; Massaiu, Ilaria; Petraglia, Laura; Leosco, Dario; Poggio, Paolo; Parisi, Valentina (Frontiers in Medicine, 2022)
Background: Cardiac amyloidosis (CA) has been recently recognized as a condition frequently associated with aortic valve stenosis (AS). The aim of our study was to evaluate: the main characteristics of AS patients with and without CA; the impact of CA on AS patients mortality; and the effect of different treatment strategies on outcomes of AS patients with concomitant CA. Materials and methods: A detailed search related to CA in patients with AS and outcomes was conducted according to PRISMA guidelines. Seventeen studies enrolling 1988 subjects (1658 AS alone and 330 AS with CA) were included in the qualitative and quantitative analysis of main AS patients characteristics with and without CA, difference in mortality, and treatment strategy. Results: The prevalence of CA resulted in a mean of 15.4% and it was even higher in AS patients over 80 years old (18.2%). Patients with the dual diagnosis were more often males, had lower BMI, were more prone to have low-flow, low-gradient with reduced left ventricular ejection fraction AS phenotype, had higher E/A and E/e’, and greater interventricular septum hypetrophy. Lower Sokolow-Lyon Index, higher QRS duration, higher prevalence of right bundle branch block, higher levels of N-terminal pro-brain natriuretic peptide, and high-sensitivity troponin T were significantly associated with CA in AS patients. Higher overall mortality in the 178 AS+CA patients in comparison to 1220 AS alone patients was observed (OR 2.25, p=0.004). Meta-regression analysis showed that younger age and diabetes were associated with overall mortality in AS patients with CA (Z-value -3.0 p=0.003 and Z-value 2.5 p=0.013, respectively). Finally, patients who underwent surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) had a similar overall mortality risk but lower than medication-treated only patients. Conclusions: Results from our meta-analysis suggest that several specific clinical, electrocardiographic, and echocardiographic features can be considered “red flags” of CA in AS patients. CA negatively affects the outcome of AS patients. Patients with concomitant CA and AS benefit from SAVR or TAVI.